Involvement of the α-helical and Src homology 3 domains in the molecular assembly and enzymatic activity of human α1,6-fucosyltransferase, FUT8 - Ihara, Hideyuki; Okada, Takahiro; Taniguchi, Naoyuki; Ikeda, Yoshitaka (Biochimica et biophysica acta. General subjects, 2020)
Previous structural analyses showed that human α1,6-fucosyltransferase, FUT8 contains a catalytic domain along with two additional domains, N-terminal α-helical domain and C-terminal Src homology 3 domain, but these domains are unique to FUT8 among glycosyltransferases. The role that these domains play in formation of the active form of FUT8 has not been investigated. This study reports on attempts to determine the involvement of these domains in the functions of FUT8. Based on molecular modeling, the domain mutants were constructed by truncation and site-directed mutagenesis, and were heterologously expressed in Sf21 or COS-1 cells. The mutants were analyzed by SDS-PAGE and assayed for enzymatic activity. In vivo cross-linking experiments by introducing disulfide bonds were also carried out to examine the orientation of the domains in the molecular assembly. Mutagenesis and molecular modeling findings suggest that human FUT8 potentially forms homodimer in vivo via intermolecular hydrophobic interactions involving α-helical domains. Truncation or site-directed mutagenesis findings indicated that α-helical and SH3 domains are all required for enzymatic activity. In addition, in vivo cross-linking experiments clearly indicated that the SH3 domain located in close proximity to the α-helical domain in an intermolecular manner. α-Helical and SH3 domains are required for a fully active enzyme, and are also involved in homophilic dimerization, which probably results in the formation of the active form of human FUT8. α-Helical and SH3 domains, which are not commonly found in glycosyltransferases, play roles in the formation of the functional quaternary structure of human FUT8. •Human α1,6-fucosyltransferase, FUT8 was proposed to be a homodimer.•α-Helical and SH3 domains are required for the enzymatic activity of FUT8.•The hydrophobic interaction of α-helical domain is involved in the dimerization.•The spatial orientation of SH3 domain is involved in the dimerization of FUT8.